Britain and the administration of the Trucial States 1947-1965 - Alhammadi, Muna M. 1976- (Emirates Center for Strategic Studies and Research, 2013)
For over 150 years, from 1820 up to the foundation of the United Arab Emirates in 1971, Britain and the emirates of the eastern Arabian Peninsula were linked by a relationship that was unique when compared to colonial models exercised elsewhere. From the signing of the General Treaty with the Arab Tribes of the Gulf in 1820, through to the oil and aviation concession agreements penned during the mid- to late-20th century, formal treaties and agreements with the rulers of the various emirates formed the basis of Britain's long influence in the region, and are discussed in detail in this study. It also explores the evolution of the area's first security force in the early 1950s - the Trucial Oman Levies (TOL), which played a key role in the security and development of the emirates